Sociality of digital transformation processes - Saltanovich, Irуna P. (Journal of the Belarusian State University. Sociology, 2024)
Technology has always been the agent of profound change in science, society and every other sphere of life. The latest technological revolution, the digital revolution, is noexception. Sociocultural relations in digital include a set of multidirectional trends reflected in sociality, testifying to the non-linearity of social development. In the article, the analysis of sociocultural changes is used to assess the impact of digital transformation. The processes of digitalisation and digitalisation processes reveal the effectiveness of the impact of technological and communicative environments on the social relations. The question of digital transformation and changes in the modern social landscape of onlife. The understanding of a person in digital transformation is revealed in the culturocentricity sociality. Technological resources, changing the rules of the game, related to information and communication technologies, in sociality it is proposed to be considered not as passive tools, but as interactive systems.
Keywords: sociality; digital transformation; culture; onlife; information and communication technologies